Redesigning of Geobacillus zalihae T1 lipase based on spacegrown crystal structure - Ishak, Siti Nor Hasmah (2019)
A microgravity environment is a favorable condition meant for growing a protein crystal, due to less sedimentation and convection. These factors would have benefited the protein crystal in terms of morphologies, crystal quality and appearance, which are important in producing a high quality electron density map. Nevertheless, the differences of structural architecture and features in protein related to the formation of hydrogen bonds and ion interactions remains unclear. In order to understand the relative contributions of a space atomic model in protein structure stability, it was necessary to compare the structure with the one grown on earth condition. There are existing limitations about manipulation of structural information for production of new enzyme due to insufficient analysis of both structures. Therefore, an earth and space condition crystal structures from a thermostable T1 lipase of Geobacillus zalihae were analyzed and compared. It was anticipated that the differences in hydrogen bonds and ion interactions are the main contributing factors towards protein stabilization. A molecular dynamics simulations approach was used to study differences of atomic fluctuations and conformational changes of both T1 lipase structures. From here, the structures stability was determined by a set of parameters comprising root mean square deviation (RMSD), radius of gyration, and root mean square fluctuation (RMSF) in which the results showed a more stable space-grown structure compared to the earth-grown structure due to the presence of more hydrogen bonds. According to the in silico data, hydrogen bond interactions at position Asp43, Thr118, Glu250 and Asn304 and ion interaction at position Glu226 were chosen to imitate the space-grown crystal structure. Following that, the impact of combined interactions in mutated structure of T1 lipase was studied. The molecular interactions of five single mutants and the one that combined all five mutations, 5M were predicted based on structural changes and energy landscape by GROMACS simulation package. Site directed mutagenesis was applied on wild-type HT1 (wt-HT1) lipase to generate five single mutants (D43E, T118N, E226D, E250L and N304E), in which these sites were further combined by a gene synthesis to generate a new mutant showing five mutation points (D43E/T118N/E226D/E250L/N304E). The native lipase wt- HT1, single mutants and 5M mutant lipases were purified by affinity chromatography showing a recovery between 49.6 to 59.9% and a purification fold of 2.5 to 3.3. All lipases exhibited high activity at 60 to 80 °C. Mutants E250L and N304E shifted in optimum temperature to 80 °C as compared to wt-HT1 lipase. All lipases showed high activity at alkaline conditions of pH 6.0 to 9.0. The thermostability study indicates the mutant E226D as the most stable lipase having prolonged half-life (T1/2) values and melting temperature. A T1/2 value of E226D was found at 28 hours, 165 minutes and 47 minutes at 60 °C, 70 °C and 80 °C, respectively where the mutant reportedly showing a melting temperature (Tm) of 77.4 ± 2.6 °C. In contrast, mutation of all five positions in the 5M mutant failed to increase the stability of lipase as the half-life at 60 °C exhibited a decline from 9 hours to 6 hours. At 70 °C and 80 °C, the half-life was found to be 23 minutes and 8 minutes, respectively. The melting temperature decreased 3.3 °C to 67.6 ± 0.8 °C. The presence of metal ions, especially calcium ion, had a positive effect on the stability of D43E, T118N, E250L and 5M lipases, which increased as more calcium was added. Meanwhile, Zn2+, Cu2+, Mg2+ and Fe3+ ions inhibited the activity of lipases. In addition, the activities of D43E, T118N and 5M lipases increased in the presence of DMSO. All lipases showed a good hydrolysis rate in natural oil, except for coconut oil. All lipases shown to have loss in activities in the presence of surfactants and sodium dodecyl sulfate (SDS). In the presence of calcium ion, the stability of 5M mutant and wt-HT1 lipases were increased towards high temperatures and organic solvents. The presence of calcium prolonged the half-life of 5M and wt-HT1, and increased the Tm at 8.4 and 12.1 °C, respectively. The combination of substituted amino acid had produced a highly stable mutant hydrolyzing oil in selected organic solvents such as DMSO, n-hexane and n-heptane. To correlate mutations in 5M mutant with its structural transition, 5M mutant lipase was subjected to crystallization in 0.5 M sodium cacodylate trihydrate, 0.4 M sodium citrate tribasic pH 6.5 supplemented with 0.2 M sodium chloride (NaCl). The protein structure was elucidated at resolution 2.64 Å with 90.9% completeness. The crystal structure of 5M mutant consists of two asymmetric units that are similar to each other, with RMSD value of 0.7789 Å after superimpositions of chains A and B. The structure analysis revealed that 5M failed to introduce hydrogen bonds and ionic interaction at the intended positions. The cumulative mutations also resulted in decreasing in molecular interactions such as hydrogen bonds and interactions. The impacts of the mutations resulted in decreasing in stability and half-life of lipase against high temperature. As a conclusion, it is difficult to emulate the cumulative interactions happened in the space-grown T1 lipase as shown by mutant 5M. Nonetheless, lipases containing a single mutant of D43E and E226D were found to be successful in introducing and increasing the mutant stability, where the stability of protein structure was highly dependent on the role of hydrogen bonds and ion interactions.